A intergeracionalidade na preparação para o casamento - Ramiro, Elana Costa (2014)
The objective of this research was to understand the process of the construction of the conjugal relationship from the sharing of intergenerational stories of a couple while preparing for marriage. In order to contextualize this study, a brief historical description of dating within the Brazilian context was presented; from the colonial period in Brazil to the current days including a discussion of the main tasks undertaken since the formation of the couple up to the of the first stage of the family life cycle and yet a presentation of what the family within an intergenerational perspective consists of. This was a qualitative research with an instrumental case outline. An engaged couple from the researcher's network of contacts was appointed and three meetings were conducted with the purpose of investigating the intergenerational stories and how this knowledge could be used in the construction process of conjugal relationship. In the meetings the instruments used were the semi-structured interviews and the genogram. This study highlighted the fact that the sharing of intergenerational stories during the marriage preparation period is essential in the process of building the conjugal relationship. The sooner the couple goes through this process; it will take more time to mature conjugal project. This study also paves the way for preventive work with couples and families in clinics, institutions and communities